Pregnancy-Associated Death in Utah: Contribution of Drug-Induced Deaths. Issue 6 (June 2019) - Smid, Marcela C.; Stone, Nicole M.; Baksh, Laurie; Debbink, Michelle P.; Einerson, Brett D.; Varner, Michael W.; Gordon, Adam J.; Clark, Erin A. S.
Abstract : OBJECTIVE: Drug-induced deaths, defined as intentional or unintentional consumption of illicit substances or diverted medications leading to death, are the leading cause of death for reproductive-age women in the United States. Our objective was to describe pregnancy-associated deaths attributed to drug-induced causes to identify opportunities for intervention. METHODS: Using the Utah Perinatal Morality Review Committee database, we performed a retrospective cohort study of all pregnancy-associated deaths—death of a woman during pregnancy or within 1 year from the end of pregnancy—from 2005 to 2014. We performed a detailed descriptive analysis of women with drug-induced deaths. We compared characteristics of women with drug-induced and other pregnancy-associated deaths. RESULTS: From 2005 to 2014, 136 pregnancy-associated deaths were identified. Drug-induced death was the leading cause of pregnancy-associated death (n=35, 26%) and 89% occurred in the postpartum period. More specifically, those with a drug-induced death were more likely to die in the late postpartum period, defined as death occurring within 43 days to 1 year of the end of the pregnancy, (n=28/35, 80%) compared with women whose deaths were from other pregnancy-associated causes (n=34/101, 34%) ( P <.001). The majority of drug-induced deaths were attributed to opioids (n=27/35, 77%), prescription opioids (n=21/35, 60%), and polysubstance use (n=29/35, 83%). From 2005 to 2014, the pregnancy-associated mortality ratio increased 76%, from 23.3 in 2005 to 41.0 in 2014. During this same time period, the drug-induced pregnancy-associated mortality ratio increased 200%, from 3.9 in 2005 to 11.7 in 2014. CONCLUSION: Drug-induced death is the leading cause of pregnancy-associated death in Utah and occurs primarily in the late postpartum period. Interventional studies focused on identifying and treating women at risk of drug-induced death are urgently needed. Abstract : Drug-induced deaths are the leading cause of pregnancy-associated death in Utah, and 89% occur in the postpartum period.